The Void Galaxy Survey: Morphology and Star Formation Properties of Void Galaxies. Issue Volume 11:Issue S308(2015) (12th October 2016) - Beygu, Burcu; Kreckel, Kathryn; van der Hulst, Thijs; Peletier, Reynier; Jarrett, Tom; van de Weygaert, Rien; van Gorkom, Jacqueline H.; Aragón-Calvo, Miguel
Abstract: We present the structural and star formation properties of 59 void galaxies as part of the Void Galaxy Survey (VGS). Our aim is to study in detail the physical properties of these void galaxies and study the effect of the void environment on galaxy properties. We use Spitzer 3.6μ and B-band imaging to study the morphology and color of the VGS galaxies. For their star formation properties, we use Hα and GALEX near-UV imaging. We compare our results to a range of galaxies of different morphologies in higher density environments. We find that the VGS galaxies are in general disk dominated and star forming galaxies. Their star formation rates are, however, often less than 1 M⊙ yr -1 . There are two early-type galaxies in our sample as well. In re versus MB parameter space, VGS galaxies occupy the same space as dwarf irregulars and spirals.